Globalization, tax competition, and the fiscal viability of the welfare state - Philipp Genschel (Max Planck Institute for the Study of Societies, 2001)
Does globalization undermine the fiscal basis of the welfare state? The conventional wisdom believes so: open borders cause tax competition, which in turn leads to a race to the bottom in capital taxation. However, the data show that revenues from capital taxation are fairly stable in OECD countries. Some observers conclude from this that globalization does not pose much of a challenge to the welfare state. This conclusion is unwarranted because it overlooks that tax competition was not the only challenge facing welfare states during the 1980s and 1990s. There was also slow growth, rampant unemployment, and high levels of precommitted spending. These problems exerted countervailing pressures that prevented a race to the bottom in taxation. Yet, this does not mean that national autonomy has not been diminished. The welfare state is trapped in between external pressures to reduce the tax burden on capital and internal pressures to maintain revenue levels and relieve the tax burden on labor.
Keywords: 300